2017
DOI: 10.1002/1873-3468.12742
|View full text |Cite
|
Sign up to set email alerts
|

From chronic overnutrition to metaflammation and insulin resistance: adipose tissue and liver contributions

Abstract: The close association of obesity with an increased risk of metabolic diseases, such as insulin resistance, type 2 diabetes, and nonalcoholic fatty liver disease, is now well established. In this review, we aim first to describe the inflammatory process activated in response to overnutrition, especially in the liver and the adipose tissue. We then discuss the systemic effects of low-grade inflammation on the onset of insulin resistance. Particular attention is given to a series of very recent reports that ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 256 publications
(268 reference statements)
0
70
0
Order By: Relevance
“…The role of obesity‐associated ATM recruitment and insulin resistance has become increasingly evident during the past several years. ATMs are important in the development and maintenance of obesity‐induced adipose tissue inflammation, fatty liver, and insulin resistance . Pan et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of obesity‐associated ATM recruitment and insulin resistance has become increasingly evident during the past several years. ATMs are important in the development and maintenance of obesity‐induced adipose tissue inflammation, fatty liver, and insulin resistance . Pan et al.…”
Section: Resultsmentioning
confidence: 99%
“…ATMs are important in the development and maintenance of obesity-induced adipose tissue inflammation, fatty liver, and insulin resistance. [27,28] Pan et al reported that mice given THC treatment reduced recruitment of M1 macrophages and showed a higher accumulation of M2 macrophages. [29] Our data have demonstrated that AWE has the potential to decrease inflammatory macrophage infiltration and polarization.…”
Section: Reciprocal Decrease In M1-type Atms With An Increase In M2-tmentioning
confidence: 99%
“…CCL2 (MCP-1) is a major factor promoting monocyte recruitment from the circulation into adipose tissue during overnutrition (32, 33). CCL2 levels are very high in both white adipose tissue and plasma in obesity (3, 31, 32, 3436).…”
Section: Discussionmentioning
confidence: 99%
“…Adipose tissue -via the secretion of hormone-like factors, named adipokines -is increasingly recognized as an endocrine and immunological organ actively participating in homeostatic mechanisms including metabolism and immune function (Schaffler et al 2005(Schaffler et al , 2006(Schaffler et al , 2007. Obesity is associated with (encompassing adipocytes, pre-adipocytes, fibroblasts, monocytes, macrophages, endothelial cells and mesenchymal stem cells) in visceral adipose tissue depots in particular (Weisberg et al 2003, Apostolopoulos et al 2016, including pro-inflammatory signaling pathway activation in adipocytes themselves (Grant & Stephens 2015, Caputo et al 2017. This pro-inflammatory transformation is pathophysiologically relevant, leading to insulin resistance and other associated co-morbidities in obese patients (Gregor & Hotamisligil 2011).…”
Section: Introductionmentioning
confidence: 99%